Unpacking the ageing–migration nexus and challenging the vulnerability trope. Issue 2 (25th January 2017) - King, Russell; Lulle, Aija; Sampaio, Dora; Vullnetari, Julie
ABSTRACT: The nexus between ageing and migration throws up a variety of situations. In this paper, we map out the various circumstances in which ageing and migration fuse together as entwined trajectories to produce situations of vulnerability, coping, active ageing and variable well-being. The ageing process is seen to be socially constructed and culturally embedded; hence, place – at 'home' or 'abroad', or some transnational mix – becomes a paramount structuring variable. Different models of successful ageing compete as migrants move and age in different countries and different cultures; the Western model of individual self-reliance should not necessarily be imposed on ageing migrant populations. In the final part of the article we challenge the prevailing trope of vulnerability applied to the perceived double disadvantage of being both an older person and a migrant, and present four case-studies in which older migrants enact agency and independence to achieve a greater level of material and subjective well-being.